Comparison of an on-farm point-of-care diagnostic with conventional culture in analysing bovine mastitis samples. Issue 2 (30th April 2019) - Jones, Geoff; Bork, Olaf; Ferguson, Scott A; Bates, Andrew
Abstract: The performance of a new point-of-care diagnostic (Mastatest), an on-farm test designed to identify bacteria and provide antibiotic sensitivity testing information from milk samples, was compared with standard microbiological culture methods. A total of 292 milk samples from clinical mastitis cases in dairy cows on New Zealand dairy farms were examined, and latent class analysis was used to estimate the performance characteristics of both tests. Two hundred and fifty-six samples (87.7%) demonstrated bacterial infection in standard culture, and 269 (92.1%) using the point-of-care diagnostic. The most common bacterial species detected was Streptococcus uberis, found in 195 samples (66.8%) using standard culture and 190 samples (65.1%) using the point-of-care diagnostic. Latent class analysis found no significant differences in test characteristics between the point-of-care diagnostic and standard culture. The estimated sensitivity and specificity of the point-of-care diagnostic against all targets combined were 94.6 and 72.1% respectively; the corresponding estimates for standard culture were 90.5 and 73.9%. Comparison of antibiotic susceptibility testing using the point-of-care diagnostic and the reference method showed similar trends and, in some cases, identical MIC50 and MIC90 values, with at most one antibiotic dilution difference.